PlaceProfile: Employing Visual and Cluster Analysis to Profile Regions based on Points of Interest - Christófano, Rafael Mariano [UNESP]; Júnior, Wilson Estécio Marcílio [UNESP]; Eler, Danilo Medeiros [UNESP] (My University, 2021)
Understanding how commercial and social activities and points of interest are located in a city is essential to plan efficient cities in smart mobility. Over the years, the growth of data sources from distinct online social networks has enabled new perspectives to applications that provide mechanisms to aid in comprehension of how people displaces between different regions within a city. To support enterprises and governments better understand and compare distinct regions of a city, this work proposes a web application called PlaceProfile to perform visual profiling of city areas based on iconographic visualization and to label areas based on clustering algorithms. The visualization results are overlayered on Google Maps to enrich the map layout and aid analyst in understanding region profiling at a glance. Besides, PlaceProfile coordinates a radar chart with areas selected by the user to enable detailed inspection of the frequency of categories of points of interest (POIs). This linked views approach also supports clustering algorithms’ explainability by providing inspections of the attributes used to compute similarities. We employed the proposed approach in a case study in the São Paulo city, Brazil.
Keywords: Area Profiling; Clustering; Google Maps; POIs; Smart Cities; Smart Mobility; Visualization